2022
DOI: 10.1101/2022.04.22.488753
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking brain organoid recapitulation of fetal corticogenesis

Abstract: Brain organoids are becoming increasingly relevant to dissect the molecular mechanisms underlying psychiatric and neurological conditions. The in vitro recapitulation of key features of human brain development affords the unique opportunity of investigating the developmental antecedents of neuropsychiatric conditions in the context of the actual patients’ genetic backgrounds. Specifically, multiple strategies of brain organoid (BO) differentiation have enabled the investigation of human cerebral corticogenesis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Other genes consistently upregulated in 7Dup in more than one stage were a group of poorly characterized zinc finger transcription factors (e.g., ZNF229, ZNF300, ZNF560, ZNF578). Focusing at each differentiation stage separately, the most outstanding observations included: i) at day 18, a modulation of cell adhesion and ECM components, mostly up-regulated in WBS COs. Of note, several of these genes (e.g., COL12A, PCOLCE, BGN, NID2, EMILI1) belong to a fetal cortex gene co-expression module characterized by non-monotonic expression pattern during cortex development and functionally associated to ECM (Cheroni et al, 2022); ii) at day 50, an upregulation in WBS COs of histone protein genes as well as RG marker Nestin, consistent with the observed increase in proliferative cells in WBSs COs. This was accompanied at the same stage with the up-regulation in 7Dup COs of dorsal forebrain commitment drivers, including FOXG1, LHX2, NEUROD6 and TBR1, whose trend of modulation was conserved in foldchange also at day 100 (Figure S4A); and, iii) the upregulation at day 100 of genes involved in synaptic transmission in WBS COs (e.g., GRIK1, GRIA4, GRIN3A).…”
Section: Q1123 Reciprocal Cnvs Causes Progenitor Proliferation and Ne...supporting
confidence: 62%
See 1 more Smart Citation
“…Other genes consistently upregulated in 7Dup in more than one stage were a group of poorly characterized zinc finger transcription factors (e.g., ZNF229, ZNF300, ZNF560, ZNF578). Focusing at each differentiation stage separately, the most outstanding observations included: i) at day 18, a modulation of cell adhesion and ECM components, mostly up-regulated in WBS COs. Of note, several of these genes (e.g., COL12A, PCOLCE, BGN, NID2, EMILI1) belong to a fetal cortex gene co-expression module characterized by non-monotonic expression pattern during cortex development and functionally associated to ECM (Cheroni et al, 2022); ii) at day 50, an upregulation in WBS COs of histone protein genes as well as RG marker Nestin, consistent with the observed increase in proliferative cells in WBSs COs. This was accompanied at the same stage with the up-regulation in 7Dup COs of dorsal forebrain commitment drivers, including FOXG1, LHX2, NEUROD6 and TBR1, whose trend of modulation was conserved in foldchange also at day 100 (Figure S4A); and, iii) the upregulation at day 100 of genes involved in synaptic transmission in WBS COs (e.g., GRIK1, GRIA4, GRIN3A).…”
Section: Q1123 Reciprocal Cnvs Causes Progenitor Proliferation and Ne...supporting
confidence: 62%
“…We generated patient-derived COs that recapitulate early to mid-fetal corticogenesis (Cheroni et al, 2022; Paşca et al, 2015; Yoon et al, 2019) from 13 iPSC lines reprogrammed from 8 affected individuals and 5 healthy controls (4-WBS, 4-7Dup and 5 CTL, Figure 1A ), including, respectively, 1 clone per individual following the design that we previously benchmarked (Germain and Testa, 2017), in order to avoid artificial inflation of spurious differential expression due to donors‘ genetic backgrounds. Array comparative genomic hybridization (aCGH) confirmed that the 7q11.23 CNV is preserved upon reprogramming ( Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…This revealed similar lineage relationships between aRG and bRG in both systems ( Camp et al, 2015 ; Pollen et al, 2015 ). Subsequent studies readily confirmed the existence of a cell population with a transcriptomic signature of bRG ( Bershteyn et al, 2017 ; Giandomenico et al, 2019 ; Pollen et al, 2019 ; Velasco et al, 2019 ; Cheroni et al, 2022 ). A recent work aimed to understand the reproducibility of organoids, identified consistent generation of diverse cell types, including bRG, in multiple forebrain organoids ( Velasco et al, 2019 ).…”
Section: What Have Organoids Told Us About Brg?mentioning
confidence: 82%